Experimental observation of fatigue degradation in a composite wind turbine blade. (15th March 2019) - Chen, Xiao
Abstract: This study reports experimental observation of structural degradation in a composite wind turbine blade subject to fatigue loading. The fatigue test is carried out according to the test standard for the blade certification. The changes of bending stiffnesses, natural frequencies and damping ratios due to fatigue are examined and discussed. The study provides the first of this kind observation on full-scale composite rotor blades in the literature.